2015
DOI: 10.1021/acs.jpcc.5b01465
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Benzene in the Breathing Metal–Organic Framework MIL-53(Cr): A Joint Experimental–Computational Investigation

Abstract: A combination of experimental (quasi-elastic neutron scattering and 2 H NMR) and computational (molecular dynamics) tools was used to uncover the molecular mobility of benzene trapped inside the flexible channel-type MIL-53 (Cr 3+ ) MOF. This material was shown to undergo a contraction of the structure upon benzene adsorption with the formation of a narrow pore phase with a smaller aperture. This confinement was found to strongly influence the dynamics of the guest: benzene diffuses in a region centered in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 71 publications
(109 reference statements)
4
39
0
Order By: Relevance
“…The pattern with <C Q > = 89 kHz and quadrupolar splitting Δν of 66.7 kHz found in Figure are typical of those reported for benzene molecules in other porous systems . The full lineshape analysis carried out in those works has demonstrated that the static deuterium quadrupolar constant (DQCC of ~180 kHz) is reduced to ~90 kHz due to the in‐plane C 6 rotation of bound benzene molecules at α = 90° as it is depicted in Figure a.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The pattern with <C Q > = 89 kHz and quadrupolar splitting Δν of 66.7 kHz found in Figure are typical of those reported for benzene molecules in other porous systems . The full lineshape analysis carried out in those works has demonstrated that the static deuterium quadrupolar constant (DQCC of ~180 kHz) is reduced to ~90 kHz due to the in‐plane C 6 rotation of bound benzene molecules at α = 90° as it is depicted in Figure a.…”
Section: Resultssupporting
confidence: 83%
“…As generally accepted, motions of guest molecules in porous solids can be probed by 2 H variable‐temperature static solid‐state NMR spectra and applying line‐shape analysis . The variable‐temperature 2 H NMR spectra obtained by the solid‐echo experiments on static sample ZrPhos‐Ben0.3 are presented in Figure .…”
Section: Resultssupporting
confidence: 67%
“…In order to (i) move MOFs toward practical incorporation as H 2 storage media, and (ii) enhance H 2 capacity in future MOFs, knowledge of the dynamic behavior of H 2 in today's MOFs is critical. SSNMR is a sensitive probe of the local nuclear electronic and magnetic environment, and provides rich information on MOFs from the perspective of the metals, 10 organic linkers, 11 guest molecules, 12 and dynamic components. 13,14 NMR interactions are generally anisotropic (directionally-dependent) with respect to the magnetic field and are influenced by dynamics in a predictable manner; rich motional information can be extracted from spectral simulations.…”
mentioning
confidence: 99%
“…[12] In addition, certain MOFs are capable of "breathing" by reversible change of the pore size upon guest molecules adsorption. [13] Despite the breathing phenomenon itself has received much attention, its effect on the molecular transport has remained poorly understood with a few exceptions, [14] again related to the hydrocarbons.…”
mentioning
confidence: 99%
“…This allows to probe the motions of the species adsorbed or confined in MOFs over a broad time scale range. [9,14,22] The phase pure MIL-53(Al) with BET surface area of 1250 m 2 g À 1 was synthesized using a previously reported procedure. [15] Details of the synthesis and characterization of the obtained material are provided in SI.…”
mentioning
confidence: 99%